Computational and Experimental Assessment of Turbulence Stimulation on Flow Induced Motion of a Circular Cylinder - Kinaci, Omer Kemal; Lakka, Sami; Sun, Hai; Fassezke, Ethan; Bernitsas, Michael M. (ASME, 2016)
Vortex-induced vibrations (VIVs) are highly nonlinear and it is hard to approach the problem analytically or computationally. Experimental investigation is therefore essential to address the problem and reveal some physical aspects of VIV. Although computational fluid dynamics (CFDs) offers powerful methods to generate solutions, it cannot replace experiments as yet. When used as a supplement to experiments, however, CFD can be an invaluable tool to explore some underlying issues associated with such complicated flows that could otherwise be impossible or very expensive to visualize or measure experimentally. In this paper, VIVs and galloping of a cylinder with selectively distributed surface roughness-termed passive turbulence control (PTC)-are investigated experimentally and computationally. The computational approach is first validated with benchmark experiments on smooth cylinders available in the literature. Then, experiments conducted in the Marine Renewable Energy Laboratory (MRELab) of the University of Michigan are replicated computationally to visualize the flow and understand the effects of thickness and width of roughness strips placed selectively on the cylinder. The major outcomes of this work are: (a) Thicker PTC initiates earlier galloping but wider PTC does not have a major impact on the response of the cylinder and (b) The amplitude response is restricted in VIV due to the dead fluid zone attached to the cylinder, which is not observed in galloping.
Keywords: vortex-induced vibrations; passive turbulence control; galloping; VORTEX-INDUCED VIBRATION; NUMERICAL-SIMULATION; SURFACE-ROUGHNESS; LOW MASS; FREQUENCY; Engineering